Fertility and sexual function in female Hodgkin lymphoma survivors of reproductive age. Issue 23 (28th June 2013) - Eeltink, Corien M; Incrocci, Luca; Witte, Birgit I; Meurs, Saskia; Visser, Otto; Huijgens, Peter; Verdonck‐de Leeuw, Irma M
Abstract : Aims and objectives: To assess the perceived fertility status and to determine the association between perceived fertility status and sexual function, as reported by young female Hodgkin lymphoma survivors. Background: Young female Hodgkin lymphoma survivors are at risk of infertility and impaired sexual function. However, little is known about their awareness of infertility and its association with sexual functioning. Design: A descriptive questionnaire survey. Methods: In this cross‐sectional study, a survey was completed by female Hodgkin lymphoma survivors (< 40 years). Outcome measures included self‐reported fertility status and sexual problems and the internationally validated Female Sexual Function Index. Results: In total, 36 survivors were included (mean age 32 years, SD 4). Eighteen women (50%) thought themselves fertile. Eight survivors (22%) who perceived themselves as being infertile were more often treated with alkylator‐based chemotherapy, and 63% reported sexual dysfunction. Ten survivors (28%) were not aware as to whether they were fertile or not; seven of these would like to have children. The reported fertility status was related to age and chemotherapy regimen. Regarding sexuality, 14 (39%) of the female Hodgkin lymphoma survivors reported one or more sexual problem and none reported recovery. Female sexual dysfunction according to the Female Sexual Function Index was reported by 11 (31%) survivors. Conclusion: Almost 30% of Hodgkin lymphoma survivors do not know whether they are fertile or not. Overall sexual dysfunction is common in Hodgkin lymphoma survivors and comparable to the general population. However, a lack of desire was significantly more often reported in female Hodgkin lymphoma survivors. Relevance to clinical practice: To prevent assumed infertility and unintended childlessness by postponing parenthood in young female survivors, awareness of fertility status is needed. There is also a need to routinely assess sexual function and provide adequate interventions to improve arousal and lubrication problems.